2016
DOI: 10.1007/s12020-016-1078-3
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution-cone beam tomography analysis of bone microarchitecture in patients with acromegaly and radiological vertebral fractures

Abstract: Editor-in-Chief: A. Giustina ▶ Covers leading topics in endocrinology ▶ Includes Hormones of reproduction, metabolism, growth, and ion balance ▶ Offers the latest on insulin and diabetes ▶ Presents newly-emerging endocrine-related topics ▶ 94% of authors who answered a survey reported that they would definitely publish or probably publish in the journal againWell-established as a major journal in today's rapidly advancing experimental and clinical research, Endocrine publishes full-length original articles dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 47 publications
4
33
0
6
Order By: Relevance
“…However, subsequent work demonstrated abnormalities in trabecular bone microstructure and strength in active acromegalic patientseven when gonadal function was normal (84,85,86). In addition to these changes in cancellous bone, the cortical bone compartment is affected, and GH excess is associated with increased cortical porosity/pore volume (81,84,87) and decreased cortical density (85).…”
Section: Effects Of Gh Excess On Bone Histomorphometry and Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…However, subsequent work demonstrated abnormalities in trabecular bone microstructure and strength in active acromegalic patientseven when gonadal function was normal (84,85,86). In addition to these changes in cancellous bone, the cortical bone compartment is affected, and GH excess is associated with increased cortical porosity/pore volume (81,84,87) and decreased cortical density (85).…”
Section: Effects Of Gh Excess On Bone Histomorphometry and Architecturementioning
confidence: 99%
“…VFs are not a simple radiological finding but they should be considered a marker of skeletal fragility, since an association between fractures and abnormalities in bone microstructure was found following the analysis of bone samples from individuals with acromegaly by histomorphometry, tridimensional dual-energy X-ray absorptiometry (DXA) of the proximal femur and peripheral HR-QCT of the bone structure at the distal radius (81,85,87).…”
Section: Effects Of Gh Excess On Fracture Riskmentioning
confidence: 99%
“…Simultaneous alterations of both cortical and trabecular alterations have been demonstrated in early histomorphologic studies . Bone turnover is increased in acromegaly; accordingly, cortical porosity has been found increased in patients with active disease and vertebral fractures, partly explaining the discrepancy between bone mass and strength. An association between cortical thickness in the hip and vertebral fractures was recently demonstrated .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acromegaly have elevated bone turnover markers (Stepan et al 1979, Scillitani et al 1997, Ueland et al 2001 but BMD as measured by DXA may not adequately estimate fracture risk (Mazziotti et al 2015). Several quantitative computed tomography studies in acromegaly patients found poorer trabecular bone parameters, such as higher trabecular separation and decreased trabecular number and bone volume to tissue volume, in comparison to healthy controls (Maffezzoni et al 2016). These conclusions are supported by studies with bone microidentation (Malgo et al 2017) and TBS (Godang et al 2016, Hong et al 2016.…”
Section: Acromegalymentioning
confidence: 98%